ON SOME SPECIES OF EUMEDONINAE FROM INDO-MALAYAN REGION - Serene, Raoul; Romimohtarto, Kasijan (Marine Research in Indonesia, 1963)
In their paper, EUMEDONINAE DU VIETNAM (Crustacea), R. Serene, T.V. Duc and N.V. Luom (1958) give an account on the genera and species of the subfamily Eumedoninae. But unfortunately some species are not sufficiently studied, especially those not collected and examined by the authors and only worked out by the reference of other publications. The present note is intended to suffice, if not all, the insufficiency in the above mentioned paper. The species studied in this note include: Proechinoecus sculptus Ward 1934. Ceratocarcinus longimanus Adams & White 1848.  Zebrida adamsi White 1847.  Rhabdonotus pictus A. Milne Edwards 1878.